2014
DOI: 10.1186/s13068-014-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of laccase-mediator treatments improving the enzymatic hydrolysis of pre-treated spruce

Abstract: BackgroundThe recalcitrance of softwood to enzymatic hydrolysis is one of the major bottlenecks hindering its profitable use as a raw material for platform sugars. In softwood, the guaiacyl-type lignin is especially problematic, since it is known to bind hydrolytic enzymes non-specifically, rendering them inactive towards cellulose. One approach to improve hydrolysis yields is the modification of lignin and of cellulose structures by laccase-mediator treatments (LMTs).ResultsLMTs were studied to improve the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…Consequently, an enhancement of saccharification yield by 13% was observed during the subsequent enzymatic hydrolysis. Similar results were attained by Moilanen et al [117,118] when acid steam-pretreated spruce was treated with C. unicolor and T. hirsuta laccases. However, using acid steam-pretreated giant read (Arundo donax), C. unicolor laccase reduced the hydrolysis yield by 17% [117].…”
Section: Pretreated Materials Laccase Treatment Effects Observed Benefsupporting
confidence: 86%
See 3 more Smart Citations
“…Consequently, an enhancement of saccharification yield by 13% was observed during the subsequent enzymatic hydrolysis. Similar results were attained by Moilanen et al [117,118] when acid steam-pretreated spruce was treated with C. unicolor and T. hirsuta laccases. However, using acid steam-pretreated giant read (Arundo donax), C. unicolor laccase reduced the hydrolysis yield by 17% [117].…”
Section: Pretreated Materials Laccase Treatment Effects Observed Benefsupporting
confidence: 86%
“…These results were comparable to those obtained with P. cinnabarinus laccase-HBT as LMS. Moilanen et al [118], in contrast, observed an increase in the lignin content of acid-steam pretreated spruce when using acetosyringone mediator together with T. hirsuta laccase. In spite of this effect, laccase-acetosyringone treatment improved the hydrolysis yield by 36%.…”
Section: Delignification By Laccase-mediator System (Lms)mentioning
confidence: 89%
See 2 more Smart Citations
“…9,10 For biological pre-treatment, laccase producing brown rot and white rot basidiomycete fungal strains have been identified as the best delignifying organisms. 11 A number of white rot fungi are reported for the biological pretreatment or simultaneous saccharification and fermentation of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%